Comportamento social e personalidade em macacos- prego (Sapajus libidinosus) residentes em área de manguezal no estado do Maranhão, Brasil - COSTA, Wanderson Oliveira da (2021)
Personality studies in capuchin monkeys (Sapajus libidinosus) are of great importance for behavioral biology. Understanding how the pattern of animal activity and individual personality works helps to draw a parallel with other primate species that share behavioral traits. Thus, the aim of this research was to investigate the social behavior and personality of a group of capuchin monkeys (Sapajus libidinosus) on a mangrove island in the state of Maranhão. In the first chapter of this dissertation we made a literature review, where we present to the reader a vast field of animal personality, its best known methods used to study the personality of non-human primates and present the characteristics of the species studied in question. In the second chapter (article), we analyze the individuals that reside in the mangrove fragment (37 ha), located on the north coast of Brazil, state of Maranhão. From the analyses, we obtained the frequency of social and agonistic behaviors, performed tests and thus we were able to understand how the group's social repertoire is organized and associate the individuals' personality.